Utilization of SysML System Models for Smart Assembly Using Digital Twins - Wilking, Fabian; Kaup, Simon; Fett, Michel; Götz, Stefan; Kirchner, Eckhard; Wartzack, Sandro (DS 130: Proceedings of NordDesign 2024, Reykjavik, Iceland, 12th - 14th August 2024, 2024)
Digital Twins are a promising technology to increase the value of products and create new business models. As models are an essential component of these Digital Twin concepts, the reuse of models is necessary. With this contribution, a methodical approach for the integration of a manufacturing structure into a system model is introduced for early verification activities. Furthermore, a novel utilization concept for transforming SysML models into discrete event models is presented to enable assembly simulations. In addition, it is embedded into a use case scenario for a Digital Assembly Twin.<br
Keywords: Systems Engineering (SE); Digital Manufacturing; Product-Service Systems (PSS); Assembly Process; SysML